INTERAKSI SOSIAL ANTAR SESAMA WARGA ASRAMA MAHASISWI RATU NIRMALA KABUPATEN KAYONG UTARA DI PONTIANAK - Januarti, Januarti; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The title of this research is "Social Interaction Between Fellow Residents of Ratu Nirmala Student Dormitory, North Kayong Regency In Pontianak". Based on the problem formulation "How is the social interaction between residents of the Ratu Nirmala female dormitory in North Kayong Regency in Pontianak" and explained based on the following sub-problems: 1. What is the form of cooperation among fellow residents of the Ratu Nirmala female student dormitory?. 2. What is the form of accommodation between fellow residents of the Ratu Nirmala student dormitory?. This study uses a qualitative method with descriptive analysis. Data collection tools used observation guidelines, interview guidelines and documentation studies. Based on the results of observations and interviews in the Ratu Nirmala student dormitory, there are 1. Social interaction in the form of cooperation between fellow residents of the Ratu Nirmala student dormitory has been well established as evidenced by the harmony and sense of kinship that is present within the residents of the Ratu Nirmala student dormitory. Living together helping each other among fellow residents of the dormitory 2. Social interaction in the form of accommodation among fellow residents of the Ratu Nirmala student dormitory has been carried out well, this is evidenced by the residents of the dormitory who live with tolerance among fellow residents of the dormitory. Make compromises or deliberation if problems occur within the dormitory environment.